Rational Altruism: Is it Possible to Reconcile Morality with Markets? - Natalia Conroy (Journal of Economic Sociology, 2017)
The book by Zsuzsa Berend is based on a decade-long ethnography of writing behavior of a “self-selected group of amazing women”, www.surromomsonline.com users (the SMO’ers). This is not the first, but probably the longest study of American surrogacy and the social dynamics of online discussions, so I'm sure it will become a “must read” for researchers of different fields. The patterns of the discussions initiated by the SMO’ers were connected to parenting and motherhood, work and relationships, contract and money, goods and gifts, which were always the concepts of interest for both economic anthropology and economic sociology. Surrogate mothers and childless couples, who entered into their dialogue without mediators (or, to be precise, via the Internet), were trying to negotiate moral meanings of these concepts in the context of market rationality and to develop a win/win project aiming to bring a new life into the world. Berend who was analyzing their rhetorical efforts by using grounded theory package tried to answer a wider question “is it possible to reconcile morality with markets?” Although she brought some theoretical concepts (in particular, from the field of economic sociology) in her analysis, she also stayed very close to her informants’ explanations of their reality. As a result and in my opinion, Berend found her answer to this question in the “native concept” of “real altruism” redefining the meaning of reciprocity and the balance of “given” and “received”.